(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2019)
The issues of borders and national foundations of state formation are of great importance in Ukraine. Ukraine is developing within the existing borders on the basis of use by the Ukrainian nation of its inalienable right for self-determination, provides the safeguard and protection of the national statehood of the Ukrainian people, and takes the lead on its territory. The inviolability of the territory of Ukraine within the existing borders implies the inviolability of these borders. The aim of this article is to characterize the safeguard and protection of the state border of Ukraine as a component of ensuring of the national security of Ukraine. The safeguard and protection of the state border are one of the important types of state activity. They are of particular relevance and importance in modern conditions after the events of 2014 and subsequent years. Earlier, the issue was the safeguard of the state border of Ukraine within the framework of law enforcement activities, but today, the issues of safeguard and reliable protection of the state border, ensuring the security of the state border and cross-border security of Ukraine are considered as important components of the country’s security and defence. In the scientific literature the content of governance in this area being considered differently. In particular, as a separate subsystem of public administration in the administrative and political sphere at the level with the management of state or military security and defence, components of national or internal security of Ukraine, etc. There is no single point of view on this matter in the theory of administrative law. Based on the analysis of the current legislation of Ukraine, the content of the concepts of national and border security of Ukraine, scientific views, available in the theory of administrative law, the author concluded that the safeguard and protection of the state border ensure the safety of the state border of Ukraine and cross-border security of Ukraine. Cross-border security, in its turn, is an element (separate subsystem) of Ukraine’s national security. Security of the state border – is protection of its inviolability and, accordingly, stability of its passing, designation, order of supply, crossing, maintenance, etc. Any violations of the state border regime must be decisively suppressed. Cross-border security – is a component of national security of Ukraine and provides security of the state border, protection of state sovereignty and territorial integrity of Ukraine within existing borders, other vital national interests of Ukraine from external and internal threats in the field of border activity (at the state border and cross-border space).